Perinatal mortality profile in municipalities of Piauí’s Coastal Plain - Silva, Gabriele Mesquita; Nunes, Adriane Saraiva; Silva, Gisele Bezerra da (Acta Scientiarum. Health Sciences, 2022)
Among the elements that impact Infant Mortality, Perinatal Mortality stands out, which involves deaths that occur during the period that begins at 22 completed weeks (or 154 days) of gestation (fetal period) and ends at 7 completed days after birth, that is, from 0 to 6 days of life (early neonatal period). The objective of this research is to describe the profile of perinatal deaths reported in municipalities of Piauí’s Coastal Plain from 2013 to 2017. This is a retrospective, descriptive study with a quantitative analysis approach, resulting from the Course Completion Work entitled ‘Perinatal mortality profile in municipalities of Piaui’s Coastal Plain’. The sample consisted of death certificates and infant death and fetal death investigation forms of children whose mothers lived in the Coastal Plain, PI, and who had their deaths confirmed in the perinatal period, between January 2013 and December 2017. During the study period, the Perinatal Mortality Rate (PMR) of the Coastal Plain, PI, was 22.97 deaths per 1,000 births, with little variation between 2013 and 2017. Fetal deaths were predominant, comprising 61.9% of the sample. Hospital deaths that occurred in Parnaíba were the most frequent, revealing this to be the reference municipality in the region. This shows the need for greater attention on the part of health professionals and managers to such conditions, in order to improve the quality of care for pregnant women, parturient women, and newborns.